Study on path independency on shape of plastic strain distribution accumulated due to long distance travel of temperature distribution - Satoshi OKAJIMA (Nihon Kikai Gakkai ronbunshu, 2019)
The prevention of excessive deformation by thermal ratcheting is important in the elevated temperature design of fast breeder reactors (FBR). In an experimental study that simulated a fast breeder reactor vessel near the coolant surface, it was reported that the long distance travel of temperature distribution causes a new type of thermal ratcheting, even in the absence of primary stress. Without excessive stress and travel distance, the inclement of the plastic strain derived from the above mechanism reduced each cycle of thermal transient, and finally reaches to approximately 0. In this paper, we investigate path independency on “saturated” distribution of plastic strain. For this purpose, we carried out several cases of finite element analyses with initial strain distribution, which simulated plastic strain distribution in the middle of accumulating. As the result, we confirmed that the shape of saturated distribution has small dependency on the shape of distribution in the middle of accumulating. Additionally, in the case using conservative initial strain distribution, further accumulation of plastic strain was not observed. This result suggests the possibility of the method that evaluate whether the accumulation of the plastic strain go beyond design limits.